2007
DOI: 10.1111/j.1572-0241.2007.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Multicenter, Placebo-Controlled Trial of Polyethylene Glycol Laxative for Chronic Treatment of Chronic Constipation

Abstract: PEG laxative is safe and effective for use in patients with chronic constipation for 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
129
3
16

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 187 publications
(152 citation statements)
references
References 10 publications
4
129
3
16
Order By: Relevance
“…The current study demonstrated that in subjects with self-reported occasional constipation, there is no significant difference between PEG 3350 and placebo in achieving relief from straining and reduction in hardness of stools experienced during BMs. PEG 3350 was generally well tolerated; AEs were similar in incidence and severity (mostly mild) between treatment groups, in line with previous reports [19,[22][23][24][25][26] . The present study used the subject's own estimation of treatment effect to evaluate whether treatment with PEG 3350 led to resolution of straining and lumpy/hard stools compared with placebo.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…The current study demonstrated that in subjects with self-reported occasional constipation, there is no significant difference between PEG 3350 and placebo in achieving relief from straining and reduction in hardness of stools experienced during BMs. PEG 3350 was generally well tolerated; AEs were similar in incidence and severity (mostly mild) between treatment groups, in line with previous reports [19,[22][23][24][25][26] . The present study used the subject's own estimation of treatment effect to evaluate whether treatment with PEG 3350 led to resolution of straining and lumpy/hard stools compared with placebo.…”
Section: Discussionsupporting
confidence: 76%
“…Also, bad defecation practices such as deferring the urge to defecate could resulted in a loss of significance between treatment arms. In the study of PEG 3350 [25] for the treatment of chronic constipation, PEG 3350 was successful in treating constipation, where success was defined as a subject experiencing ≥ 3 satisfactory BMs per week and having no more than one of the remaining three Rome III symptoms. The same study also reported that PEG-treated subjects had higher incidences of complete spontaneous BMs over placebo [25] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations